1993
DOI: 10.1159/000114159
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Pathways Linking Social and Environmental Cues to Endocrine Control Regions of Amphibian Forebrains

Abstract: The secretion of gonadotropin releasing hormone (GnRH), and hence sex steroids, is influenced by social signals produced by conspecifics and by environmental cues such as day length. The sensory systems processing these varied signals must therefore connect with the GnRH control centers in the preoptic area and hypothalamus. Forebrain pathways in frogs provide a model for how vertebrates accomplish this. Auditory information, which can transmit the features of the vocal communication signals used by frogs duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 26 publications
(40 reference statements)
2
27
1
Order By: Relevance
“…Similar phenomena in which vocal signals from a sender influence the physiology and neurobiology of a receiver have also been described in anuran amphibians Wilczynski et al, 2005). This is possible because in anurans, the central auditory system sends projections into the anterior and central thalamic nuclei, which relay auditory information into the anterior preoptic area as well as the ventral hypothalamus (reviewed in Wilczynski et al, 1993). Consequently, hypothalamic neurons respond to acoustic stimulation in male (Wilczynski and Allison, 1989;Allison, 1992) and female (Hoke et al, 2005) anurans.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar phenomena in which vocal signals from a sender influence the physiology and neurobiology of a receiver have also been described in anuran amphibians Wilczynski et al, 2005). This is possible because in anurans, the central auditory system sends projections into the anterior and central thalamic nuclei, which relay auditory information into the anterior preoptic area as well as the ventral hypothalamus (reviewed in Wilczynski et al, 1993). Consequently, hypothalamic neurons respond to acoustic stimulation in male (Wilczynski and Allison, 1989;Allison, 1992) and female (Hoke et al, 2005) anurans.…”
Section: Introductionmentioning
confidence: 59%
“…The mechanism by which estradiol concentrations are elevated in females exposed to mate choruses is explained by neuroanatomical and neurophysiological studies describing the pathway by which acoustic signals may influence central endocrine control centers (reviewed in Wilczynski et al, 1993). In anurans, ascending auditory pathways project to the preoptic area (POA) and the caudal hypothalamus via the auditory midbrain nucleus (referred to as the torus semicircularis, TS) and the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…However, animals fine-tune reproduction to coincide with times when other environmental factors, such as ecological and social conditions, are favourable (Perrins 1970;Bronson 1989;Wilczynski et al 1993). These fluctuating less predictable environmental cues, termed 'essential supplementary information' (Wingfield 1983), are integrated independently of predictive cues (Ball 1993) such that reproduction is Proc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Schmidt [38, 39]and others [23, 40, 41]have shown that in frogs, electrical stimulation of this region triggers, while ablation decreases reproductive behavior. In addition, the POA receives projections from two auditory nuclei, the anterior thalamic nucleus, and the secondary isthmal nucleus [42, 43, 44]. All together, these studies strongly implicate the POA as a structure integral for mediating acoustic communication and reproductive behavior in anuran amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Caudal hypothalamic neurons receive auditory input related to mating calls [42, 43, 44, 60, 61, 62]. Finally, sex steroid-binding sites are also present in high concentration there [22, 24, 63].…”
Section: Discussionmentioning
confidence: 99%